The The Influence of Green Investment and CSR on the Firm Value of Energy Sector Companies: The Mediating Role of Financial Performance - Juanda, Dinda Nurul; Yumna, Aimatul (Jurnal Economic Resource, 2025)
Amidst the challenges of global climate change and increasing demands for sustainability, companies are expected to focus not only on financial aspects but also on non-financial aspects such as implementing environmentally and socially responsible business practices to support the assessment of corporate value in the eyes of investors. This study aims to analyze the impact of green investments and corporate social responsibility (CSR) on corporate value, as well as to test the role of financial performance as a mediating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The research sample included 45 energy sector companies, but only nine companies met the criteria. The results revealed that green investments and CSR did not have a significant impact on corporate value, and green investments also did not affect financial performance. However, CSR was found to have a significant influence on financial performance. On the other hand, financial performance had no significant impact on corporate value. It did not act as a mediator in the relationship between green investment, CSR, and corporate value. These findings suggest that while CSR can improve financial performance, it is insufficient to increase corporate value without additional supporting factors directly. This study suggests that companies, particularly those in the energy sector, should prioritize environmental and social considerations in their operations. For green investments to support the company's value, companies must demonstrate measurable long-term benefits and align their sustainability efforts with stakeholder expectations. Furthermore, investors consider non-financial factors such as the implementation of tangible environmental performance and transparent CSR practices, thereby encouraging companies to adopt sustainability not only as a regulatory obligation but also as a strategic asset.